Innovations in Treatment Delivery, Risk of Peritonitis, and Patient Retention on Peritoneal Dialysis. Issue 2 (8th January 2017) - Piraino, Beth
Abstract: Early innovations in the delivery of peritoneal dialysis (PD) markedly improved its acceptability and lowered peritonitis rates. The standard osmotic agent was, and continues to be dextrose, an agent that is not ideal as it is readily absorbed. The development of icodextrin‐containing dialysis fluid has allowed a long dwell time to provide more effective ultrafiltration. The development of a smaller, more easily used automated cycler, led to an increase in the proportion of patients on the cycler as opposed to CAPD. Recently, new cyclers with better teaching tools and ease of use and communication with the training team have come on the market; data on outcomes using these cyclers are not yet available. Peritonitis continues to be a serious complication of PD although improvements in connectology and research on Staphylococcus aureus carriage have decreased peritonitis risk. Peritonitis rates continue to vary tremendously from one program to another, which may be in part due to failure to follow best demonstrated practices in training, care of the l catheter exit site, and prevention of peritonitis. Peritonitis rates should be expressed as episodes per year at risk and as organism‐specific rates to allow comparisons from one program to another, from one period to another and from a program to the published literature. The term technique failure is misused in PD. Patients leave PD for a host of reasons including transplantation. Transfer from PD to hemodialysis can be planned and have an excellent outcome or can be delayed or done emergently and have a less optimal outcome. The life plan of the patient with ESRD needs to be not only considered but also periodically revised as circumstances and patient wishes change.